Theory of fuel control on dual-fuel systems of gasoline engines using hydro from water electrolysis by solar energy - Vo, Xuân Thành; Do , Văn Dũng; Hoang, An Quốc (Journal of Technical Education Science, 2015)
This article presented the theoretical basis for dual-fuel hydrogen-gasoline system on gasoline engines. Hydrogen fuel is an alternative fuel with the suitable properties can be used as the second fuel on dual-fuel system on gasoline engine to improve engine performance and exhaust gas emission. On the dual-fuel system, hydrogen is supplied directly from water elec- trolysis by solar energy. The hydro fuel is formed of hydrogen and oxygen (HHO). The ratio of hydrogen and oxygen in HHO obtained during electrolysis is 2:1. The air/fuel ratio of the mix- ture was found. The modeling of the dual-fuel system was performed, thereby the fuel equations were found. The fuel equations are presented accurately and completely will be a theoretical basis for simulations and experiment.